Objective and Subjective Dimensions of University Academic Performance: a Relational Analysis - Díaz Ponce-Madrid, Aldara María (2026)
Introduction. In higher education, academic performance is one of the most powerful indicators when evaluating the success or failure of students’ educational paths and, in turn, corresponds to one of the main indicators of the quality of academic programs. Objective. To determine the factors that influence university academic performance and the relationship between its objective and subjective dimensions. Method. A quantitative, cross-sectional correlational design was used. Three hundred and twenty university students participated using purposive non-probability sampling. The University Academic Performance Scale (RAU) was administered virtually using Google Forms to measure the subjective dimension of academic performance. Data analysis was performed using JASP v19, where descriptive and correlational analyses were conducted using Kendall’s Tau-B non-parametric test. Results. University students reported average levels of academic performance, improving their results as they progress through their educational path, given that only the necessary time is dedicated to completing school tasks or activities. Conclusions. A statistically significant relationship was found between factors in the objective and subjective dimensions of academic performance. Specifically, when students increase the time they dedicate to studying, their ability to organize the resources necessary for learning improves. These findings imply the need to design interventions that strengthen time management and organization, especially for working students.